Reading Pakeha? : fiction and identity in Aotearoa New Zeland - Stachurski, Christina (Amsterdam : Rodopi, 2009)
Explains how concepts of race and ethnicity intersect with those of gender, sex and sexuality.
Includes bibliographical references and index
Keywords: Feminist fiction, English -- New Zeland -- History and criticism; New Zeland literature -- Maori authors -- History and criticism